Assessment of various bone grafts and membranes used for socket preservation - an institutional based retrospective study - AHAMED A, ASHIK; GANESH S, BALAJI; RAKSHAGAN V (The journal of contemporary issues in business and government, 2020)
The loss of alveolar bone may be attributed to various factors such as periodontitis, facial trauma, endodontic pathology and other aggressive steps used during extraction. Socket preservation is a technique in which the extraction sockets were completely filled with a bone substitute material or sealed with membranes in order to prevent bone loss. For a dental practitioner, it is important to have a clear knowledge regarding various bone grafts and membranes used for socket preservation. The aim of the study was to evaluate various bone grafts and membranes used for socket preservation. The participants were patients who reported to Saveetha Dental College for socket preservation procedure. A total of 25 patients had undergone socket preservation procedure during the specified time period. The data were collected and statistical analysis was done using IBM SPSS version 20.0. Patients in the age group of 19-30 years had highly undergone socket preservation procedure. The procedure was carried out mostly in males than females. The most commonly used graft was found to be Bio Oss (60%) and the most commonly used membrane was GTR combined with PRF (48%). Association between site of socket preservation and types of bone graft used was found to be statistically significant ( p-value: 0.001). From the present study, it can be concluded that patients in the age group of 19-30 years had highly undergone socket preservation procedure. The procedure was carried out mostly in males than females. Maxillary anteriors was the most common site. Bio-oss was the most commonly used bone graft and GTR with PRF was the most commonly used membrane among patients who had undergone socket preservation procedure.